Diffusing participatory budgeting knowledge: lessons from Korean-language research. Issue 3 (2nd July 2020) - Cho, B. Shine; No, Won; Park, Yaerin
Abstract : This study aims to expand the collective knowledge on participatory budgeting by drawing insights from studies of Korean participatory budgeting. From a review of 93 peer-reviewed journal articles published between 2003 and 2017 in the Korean language, we present a bibliometric network, a review of the research methods, and the themes of the studies. The findings suggest that participatory budgeting studies in South Korea developed upon both studies of participatory budgeting from Porto Alegre, Brazil, and studies of public budget participation mechanisms rooted in the United States. In addition, the findings demonstrate the distinctiveness of Korean participatory budgeting practices and studies, such as institutionalisation and diffusion, and impact factors that enabled successful participatory budgeting implementation.